Stimulation of Seed Viability by Means of Dispersed Solutions of Copper and Silver Nanoparticles - S.N. Maslobrod; Yu.A. Mirgorod; V.G. Borodina; N.A. Borsch (Журнал нано- та електронної фізики)
It was shown that water dispersed solutions at different concentration of copper (NPCu) and silver (NPAg) nanoparticles substantially influence germination of seeds of grain and vegetable crops. Stimulating effect was revealed after application of ultra-low concentrations NPCu (up to 10 – 17 mg/l) and NPAg (up to 10 – 13 mol/l). Treatment of seeds with sol boosts their resistance to fungal pathogens and low temperature and also increases productivity of plants in the field environment.